2012
DOI: 10.1039/c1jm13765d
|View full text |Cite
|
Sign up to set email alerts
|

A “thiol-ene” photo-curable hybrid fluorinated resist for the high-performance replica mold of nanoimprint lithography (NIL)

Abstract: Functional polyhedral oligomeric silsesquioxane (POSS)-based materials have been developed as an ideal material with high performance for nanoimprint lithography (NIL). A novel fluorinated hybrid resist as a soft mold for NIL, based on thiol-ene photopolymerization, was precisely designed and synthesized and is comprised of fluorinated mercaptopropyl polyhedral oligomeric silsesquioxane (POSS-F-SH) and a diluted crosslinker (2,2,3,3,4,4,5, DCFA 4 ). The obtained fluorinated hybrid resists possess a variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 47 publications
1
35
0
1
Order By: Relevance
“…1H,1H-Perfluoro-1-decylallyl ether and its perfluoro-1-heptyl homologue were synthesized in a one-step process by using fluorinated alcohols and allyl chloride. 159 An interesting example of fluorinated thiol was reported by Lin et al 160 based on the following silsesquioxane (POSS) containing −SH functions:…”
Section: Fluorinated Thiol−ene Systemsmentioning
confidence: 99%
“…1H,1H-Perfluoro-1-decylallyl ether and its perfluoro-1-heptyl homologue were synthesized in a one-step process by using fluorinated alcohols and allyl chloride. 159 An interesting example of fluorinated thiol was reported by Lin et al 160 based on the following silsesquioxane (POSS) containing −SH functions:…”
Section: Fluorinated Thiol−ene Systemsmentioning
confidence: 99%
“…Due to the excellent mechanical and physical properties, thiol-ene polymer has been used widely as the nanoimprint resist in NIL to fabricate high-resolution nanostructures [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…45 It was found that the movement of chains was retarded by the presence of POSS. [47][48][49][50][51][52] Thiol-ene reaction has attracted much attention and has been studied in many systems. Furthermore, POSS was only attached to the SBS chain forming new physical crosslinking sites which limited the reinforcing effect for the polymer.…”
Section: Introductionmentioning
confidence: 99%